Immune responses against a liver-stage malaria antigen induced by simian adenoviral vector AdCh63 and MVA prime-boost immunisation in non-human primates. - Capone, S; Reyes-Sandoval, A; Naddeo, M; Siani, L; Ammendola, V; Rollier, C; Nicosia, A; Colloca, S; Cortese, R; Folgori, A; Hill, A (2010)
Malaria is a major health problem as nearly half of the human population is exposed to this parasite causing around 600 million clinical cases annually. Prime-boost regimes using simian adenoviral vectors and MVA expressing the clinically relevant Plasmodium falciparum ME.TRAP antigen have shown outstanding protective efficacy in mouse models. We now extend those observations to macaque monkeys. Immunisation with AdCh63 elicited a median response of 869 IFN-γ SFC/million PBMCs to ME.TRAP and responses were boosted by MVA to reach 5256 SFC/million PBMCs, increasing at the same time the breadth of the T cell responses to cover the complete ME.TRAP antigen. Intramuscular vaccination was more immunogenic than the intradermal route, and MVA could be used repeatedly for up to 3 times to boost adenovirus-primed responses. An interval of 16 weeks between repeated MVA injections was optimal to enhance cytokine production by T cells and improve the CD8 multifunctional responses. Antibodies to TRAP were exceptionally high and maintained for a long period of time after the prime-boost regime. These results in non-human primates highlight the potential of this vaccination regime and encourage its future use in clinical trials.